Asymptotic Representations for the Solutions of One Class of Nonlinear Differential Equations of the Second Order - Shlepakov, O. R. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish asymptotic representations for the solutions of one class of nonlinear differential equations of the second order with rapidly and regularly varying nonlinearities.